2018
DOI: 10.3389/fimmu.2018.02271
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Inflammatory Gene Expression Profiling in Dry Eye Disease: Correlations With HLA-DRA and HLA-DRB1

Abstract: Purpose: In several multicenter clinical trials, HLA-DR was found to be a potential biomarker of dry eye disease (DED)'s severity and prognosis. Given the fact that HLA-DR receptor is a heterodimer consisting in an alpha and a beta chain, we intended to investigate the correlation of inflammatory targets with the corresponding transcripts, HLA-DRA and HLA-DRB1, to characterize specific targets closely related to HLA-DR expressed in conjunctival cells from patients suffering from DED of various etiologies.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 86 publications
3
27
0
1
Order By: Relevance
“…Our results showing increased XBP-1 and STAT1 levels agree with the literature and with our previous publication that showed increased XBP-1 and GRP78 in the SS KCS conjunctiva compared to healthy controls (11). Increased levels of STAT1 have been previously reported in humans and animal models, also in the conjunctiva (13,14,62,109). XBP-1 (X-box binding protein-1) participates in ER stress and UPR, decreasing salivary gland protein secretion (110).…”
Section: Genessupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showing increased XBP-1 and STAT1 levels agree with the literature and with our previous publication that showed increased XBP-1 and GRP78 in the SS KCS conjunctiva compared to healthy controls (11). Increased levels of STAT1 have been previously reported in humans and animal models, also in the conjunctiva (13,14,62,109). XBP-1 (X-box binding protein-1) participates in ER stress and UPR, decreasing salivary gland protein secretion (110).…”
Section: Genessupporting
confidence: 92%
“…Previous studies have identified a significant role for inflammation in the conjunctiva of SS KCS patients (6,13,14,34). To gain insight into the pathways involved, we analyzed which DEGs have been annotated or identified in immune pathways using the ROSALIND software and nCounter software, using the gene set analysis.…”
Section: Differential Pathways Are Activated In the Conjunctiva Of Ss Kcs Patientsmentioning
confidence: 99%
“…4). Moreover, in human corneal epithelial cells, IRF-1 levels increased after a bacterial challenge, for example, Pseudomonas aeruginosa, which played an important role in MHC class II gene expression in macrophages [50]. However, interestingly, flavonoids selectively induce IRF-1 degradation in intestinal epithelial cells [51] in which there are many flavonoids in the EEDK.…”
Section: Discussionmentioning
confidence: 99%
“…При помощи проточной цитометрии HLA-DR был обнаружен в эпителиальных клетках конъюнктивы у пациентов с ССГ. Авторами было высказано предположение о наличии прямой зависимости между количеством найденного HLA-DR и тяжестью течения ССГ, однако в ходе дальнейших исследований гипотеза не подтвердилась [50]. заключение В изученном материале предпринята попытка обобщения современных данных об этиологии и патогенезе ССГ.…”
Section: современные представления о патогенезе синдрома «сухого глаза»unclassified